Physical And Chemical Characterization Of Clay Deposits For Ree Utilization - Mohd Akhir, Mohamad Adli (Universiti Sains Malaysia, 2022)
Rare Earth Elements (REE) are potential resources to meet the advanced technologies currently as its usage have been discovered in 1955 as part of the significant component in television manufacture. Since China has reduced REE export limitations due to environmental protection measures, alternative REE resources are initiated widely. This study characterized ion adsorption clay (IAC) deposit from Kenering, Perak physically and chemically through particle size analysis, petrological, mineral phase identification, and geochemistry study. Based on physical characterization, the samples on the top are mainly dark- to reddish-brown soil indicates moist texture on its physical appearance. The weightage of the average particle size is abundance in coarser size (> 100 μm) relatively. It comprises high content of K Feldspar and quartz mineral and its accessory minerals contain of biotite and garnet minerals. When plotted on IUGS Classification, the sample can be categorized as syenite (weathered). The mineral phase identification indicates the sample is governed by quartz, kaolinite, microcline, and clay minerals such dickite. SiO2 element was the highest concentration followed by Al2O3 based on X-ray Fluorescence (XRF) analysis. Based on TAS diagram, most of the sample were scattered in syenite and diorite group. The sample enriched with LREE as La element dominating the chondrite normalized graph. The LREE and HREE concentration shows significant different which 23.19 ppm and 4.74 ppm respectively. In general, the study reveals that the sample is plutonic igneous rock (weathered) and have a significant value on demanded elements of REE. Hence, it is prospective to be mined in future.